2018
DOI: 10.1051/matecconf/201815603025
|View full text |Cite
|
Sign up to set email alerts
|

Bioethanol Production via Syngas Fermentation

Abstract: Abstract. Bioconversion of C-1 carbon in syngas through microbial fermentation presents a huge potential to be further explored for ethanol production. Syngas can be obtained from the gasification of lignocellulosic biomass, by which most of carbon content of the biomass was converted into CO and CO2. These gases could be further utilized by carbon-fixing microorganism such as Clostridium sp. to produce ethanol as the end product. In order to obtain an optimum process, a robust and high performance strain is r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…As suggested in a previous study, it is possible for the high availability of electrons from CO and H2 oxidation to induce ethanol production as a mixed growth-associated product, which was also observed in our study (Hurst & Lewis, 2010). (Anggraini et al, 2018) b values were calculated at 7 days' fermentation c lower specific growth rate in HFM-supported bioreactor due to biofilm formation on the membrane surface from bioreactor-to-membrane shells liquid recirculation d not determined…”
Section: Syngas Fermentation Performance In Hfm-supported Bioreactorsupporting
confidence: 66%
See 2 more Smart Citations
“…As suggested in a previous study, it is possible for the high availability of electrons from CO and H2 oxidation to induce ethanol production as a mixed growth-associated product, which was also observed in our study (Hurst & Lewis, 2010). (Anggraini et al, 2018) b values were calculated at 7 days' fermentation c lower specific growth rate in HFM-supported bioreactor due to biofilm formation on the membrane surface from bioreactor-to-membrane shells liquid recirculation d not determined…”
Section: Syngas Fermentation Performance In Hfm-supported Bioreactorsupporting
confidence: 66%
“…A comparison between the HFM-supported bioreactor and other fermentation systems examined in our study revealed the potential of the membrane to provide high CO mass transfer efficiency. By employing the same strain of C. ljungdahlii as a previous study on serum bottle fermentation, Anggraini et al (2018) observed a lower ethanol titer despite the presence of a high ethanol-to-acetate ratio, which corresponded to the low density of cells. This may have been caused by a limited CO gas supply ( Table 1).…”
Section: Comparison With Other Studiesmentioning
confidence: 68%
See 1 more Smart Citation
“…In the fermentation process, the pH of the fermenter is controlled so that it is not lower than 4.5 to avoid cell death, and pH control is carried out with 2M HCl and 2M NaOH solutions. Details configuration of the bioreactor used was described in Anggraini [25].…”
mentioning
confidence: 99%